Rethinking Totalitarianism and Resistance in Suzanne Collins’ The Hunger Games (2008) - BENALI ,Maroua; MOUISSA, Fattoum (University of Ammar Theledji -Laghouat, 2021)
The Hunger Games portrays a future post-apocalyptic description of a society where science fiction plays a part in an attempt to maintain power and dehumanize people seeking control. Collins successfully examines how science and technology can be used to enslave people and prevent them from having their rights, such as the right to speak up, be free, and choose their fate. Hence, this research dissertation throws an analysis on the interplay between the notions of resistance and totalitarianism. As a result, the analysis depicts how resistance can be claimed in a society that abolishes such ideals that trigger its system's collapse. This study is based on a historical approach due to the criticality of the historical context of the novel from a post-apocalyptic perspective. Yet, this research focuses on the aspects of resistance and totalitarianism in the novel. Nonetheless, this work attempts to provide an understanding of the novel's projection of totalitarianism and resistance through the use of a humanistic and psychological approach to analyzing the psychology of the characters and their nature when it comes to survival. Meanwhile, this research is also based on a descriptive-analytical method in order to describe the different characters' settings of the capitol and the districts. Thus, it is useful to investigate the districts' reactions to the capitol's oppressive and controlling regime